Implementasi E-Tilang Bagi Pelanggar Lalu Lintas di Kabupaten Jember Berdasarkan Peraturan Pemerintah Nomor 80 Tahun 2012 Tentang Tata Cara Pemeriksaan Kendaraan Bermotor di Jalan dan Penindakan Pelanggaran Lalu Lintas dan Angkutan Jalan - Rindang, Dhana Dharu; Suryo, Pramukhtiko (Indonesian Journal Publisher, 2023)
The traffic challenges faced by the Indonesian nation today are traffic violations, traffic jams and traffic crimes. These traffic violations can give rise to new problems that have more fatal consequences, for example they can result in traffic accidents and increase the death rate due to traffic accidents. The government's effort to respond to this is by instructing it to use information and communication technology to improve effective, excellent service and efficiency of public services and support transparency of public services. With a government policy related to providing services to the public using electronic services, the Chief of the Republic of Indonesia Police (KAPOLRI) then realized or implemented this policy by creating an electronic ticketing service (e-Tilang). The e-Tilang program has been implemented in Jember Regency since 2021. The implementation of the e-Tilang system in Jember Regency is still not optimal because there are many factors that hinder the realization of traffic order. So, this also has a big influence in measuring the effectiveness of implementing the e-Tilang system. This research uses a statutory approach and a conceptual approach, with a normative juridical research type. The implementation of e-Tilang in Jember Regency originally used CCTV cameras or what is usually called Electronic Traffic Law Enforcement (ETLE). However, the implementation is still not optimal, therefore to perfect the e-Tilang technology there is INCAR innovation using a mobile camera. The implementation of e-Tiling for traffic violators in Jember Regency has not been implemented optimally. Because, law enforcement for traffic violators in Jember Regency still requires the use of manual ticketing methods. So, it is necessary to improve the e-Tilang system which has been implemented throughout Indonesia, especially the new innovation, namely the INCAR car.